Sustainable Lightweight Concrete Using Candlenut Shell as Coarse Aggregate: The Impact of Water-Cement Ratios on Strength and Density - Hasrul, Muhammad Reza; Rahman, Mohammad Junaedy; Helmy, Ahnaf Riyandirga Ariyansyah Putra; Natsir, Taufiq; Asrib, Ahmad Rifqi (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
This study explores the promising potential of Candlenut Shell Aggregate (CSA) as a sustainable and innovative alternative for lightweight concrete production. Derived from Aleurites moluccanus, CSA is an agricultural by-product characterized by its low density, moderate abrasion resistance, and high water absorption make it suitable for non-structural applications like wall panels and flooring. However, integrating CSA into concrete mixes requires careful management of the water-cement (w/c) ratio which significantly affects compressive strength, density, and workability. Concrete mixes were prepared using the absolute volume method, with w/c ratios ranging from 0.65 to 0.30, to identify the optimal balance. The absolute volume principle was applied for all mix designs. Our results indicate that an optimal w/c ratio of 0.55 yields the most favorable balance, achieving the highest compressive strength of 14.3 MPa and a maximum density of approximately 1850 kg/m3. This specific ratio strikes an ideal equilibrium between adequate cement hydration and effective void minimization within the concrete matrix. Conversely, higher w/c ratios lead to increased porosity, diminishing both strength and density, while lower ratios impair workability, hindering compaction and hydration, ultimately degrading performance. These findings resonate strongly with existing prior research, further emphasizing the crucial need for pre-treatment of CSA, such as soaking or the strategic incorporation of admixtures, to effectively mitigate its inherent high absorption and enhance overall mix performance. In conclusion, this study robustly confirms the feasibility of utilizing CSA as a lightweight aggregate. This represents a significant step towards developing an eco-friendly solution that not only contributes to global sustainability goals by repurposing agricultural waste but also actively reduces reliance on conventional, resource-intensive aggregates. Future research should explore the long-term durability of CSA-based concrete and investigate advanced admixtures to further enhance its properties for broader applications.